Peran Penting Pendidikan Islam dalam Kehidupan Manusia - Ardiansyah, Rizky Septino; Imam Baihaqi Rahmatain (Medan Resource Center, 2023)
The purpose of this research is to determine the role of Islamic education in human life. while the method used in this research is qualitative, namely a scientific method that emphasizes collecting references. The importance of education is widely agreed upon by every element of society. Islamic education, which in its historical movement has always aimed at the progressivity and transformativeness of human life, so that its existence must also contain everything that humans need, not only has a pragmatic dimension, but also idealistic, not only profane, but also sacred, and not only full of content. knowledge, but also morals. The essence of Islamic education is carried out as an effort towards changes in behavior that are